Systematic analysis of a mitochondrial disease‐causing ND6 mutation in mitochondrial deficiency. Issue 5 (12th March 2020) - Chen, Deyu; Zhao, Qiongya; Xiong, Jingting; Lou, Xiaoting; Han, Qinxia; Wei, Xiujuan; Xie, Jie; Li, Xueyun; Zhou, Huaibin; Shen, Lijun; Yang, Yanling; Fang, Hezhi; et al.
Abstract: Background: The m.14487T>C mutation is recognized as a diagnostic mutation of mitochondrial disease during the past 16 years, emerging evidence suggests that mutant loads of m.14487T>C and disease phenotype are not closely correlated. Methods: Immortalized lymphocytes were generated by coculturing the Epstein–Barr virus and lymphocytes from m.14487T>C carrier Chinese patient with Leigh syndrome. Fifteen cytoplasmic hybrid (cybrid) cell lines were generated by fusing mtDNA lacking 143B cells with platelets donated by patients. Mitochondrial function was systematically analyzed at transcriptomic, metabolomic, and biochemical levels. Results: Unlike previous reports, we found that the assembly of mitochondrial respiratory chain complexes, mitochondrial respiration, and mitochondrial OXPHOS function was barely affected in cybrid cells carrying homoplastic m.14487T>C mutation. Mitochondrial dysfunction associated transcriptomic and metabolomic reprogramming were not detected in cybrid carrying homoplastic m.14487T>C. However, we found that mitochondrial function was impaired in patient‐derived immortalized lymphocytes. Conclusion: Our data revealed that m.14487T>C mutation is insufficient to cause mitochondrial deficiency; additional modifier genes may be involved in m.14487T>C‐associated mitochondrial disease. Our results further demonstrated that a caution should be taken by solely use of m.14487T>C mutation for molecular diagnosis of mitochondrial disease. Abstract : Mitochondrial DNA 14487T>C mutation at MT‐ND6 is insufficient to cause mitochondrial deficienc. Some additional modifier genes may be involved in m.14487T>C‐associated mitochondrial disease.